2013
DOI: 10.1037/a0033289
|View full text |Cite
|
Sign up to set email alerts
|

Multisensory integration, aging, and the sound-induced flash illusion.

Abstract: The present study examined age-related differences in multisensory integration and the role of attention in age-related differences in multisensory integration. The sound-induced flash illusion---the misperception of the number of visual flashes due to the simultaneous presentation of a different number of auditory beeps---was used to examine the strength of multisensory integration in older and younger observers. The effects of integration were examined when discriminating 1–3 flashes, 1–3 beeps, or 1–3 flash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
112
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(124 citation statements)
references
References 68 publications
12
112
0
Order By: Relevance
“…Small and Prescott (2005) postulated that taste, odour, and associated tactile sensations are integrated in these oral somatosensory areas, to produce a unitary flavour percept. In line with these findings, previous studies showed increased multisensory integration in older compared to young adults for visual-auditory stimuli (DeLoss, Pierce, and Andersen, 2013;Peiffer et al, 2009), as reflected in increased activity in posterior parietal integration areas in older adults (Diaconescu et al, 2013). In addition to the secondary somatosensory area, identified on the posterior insular region, the insula has been subdivided in two other anatomically and functionally meaningful regions (Deen et al, 2011;Nelson et al, 2010).…”
Section: Psychophysiology Of Age-related Changes In Taste Perceptionsupporting
confidence: 60%
“…Small and Prescott (2005) postulated that taste, odour, and associated tactile sensations are integrated in these oral somatosensory areas, to produce a unitary flavour percept. In line with these findings, previous studies showed increased multisensory integration in older compared to young adults for visual-auditory stimuli (DeLoss, Pierce, and Andersen, 2013;Peiffer et al, 2009), as reflected in increased activity in posterior parietal integration areas in older adults (Diaconescu et al, 2013). In addition to the secondary somatosensory area, identified on the posterior insular region, the insula has been subdivided in two other anatomically and functionally meaningful regions (Deen et al, 2011;Nelson et al, 2010).…”
Section: Psychophysiology Of Age-related Changes In Taste Perceptionsupporting
confidence: 60%
“…For example, using the double-flash illusion, Wallace and colleagues have shown that children with autism spectrum disorder perceive illusory flashes over an wider range of SOAs, suggesting an extended multisensory binding window compared to typically developing children (Foss-Feig et al 2010;Stevenson et al 2014;Wallace and Stevenson 2014). Similarly, normal aging seems to increase multisensory integration (Diederich et al 2008;DeLoss et al 2013), as evidenced by broader temporal binding window (Laurienti et al 2006). Presumably, age-related declines in multisensory binding result from a slowing in peripheral sensory processing, resulting in a decrease in the ability to parse multiple sensory representations (Diederich et al 2008).…”
Section: Experience-dependent Changes In Multisensory Perceptionmentioning
confidence: 95%
“…Given that multiple beeps cannot be presented simultaneously, this task includes an inherent temporal asynchrony, and studies of younger adults have shown that larger TBWs are associated with an increased perception of this illusion [53]. Recent work has shown that older adults are more susceptible to the sound-induced flash illusion [69]. A second study utilizing this illusion kept the single flash and one beep simultaneous while parametrically varying the presentation of the second beep, ranging from preceding the beep/flash pair by 270 ms to lagging by 270 ms in 40 ms steps.…”
Section: Introductionmentioning
confidence: 99%